SKEPTISISME KEOTENTIKAN HADITS DALAM PERSPEKTIF ORIENTALIS - Wely Dozan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
This paper explains the hadith in an Orientalist perspective. His study of the hadith in his book is known as the projecting back theory which states that, the hadith did not originate from the Prophet but the pathway of narratives made by the companions arbitrarily after the 2nd century Hijri. Specifically, this study aims to analyze the parts that are considered as important points including: First, the basic concept of projecting back theory. Second, the analysis of the Schacht methodology against the Sunnah. Third. trace the path of the Schacht transmission in the theory of Comon Link. Fourth, the contribution of Muslim thought to maintain the authenticity of a hadith. Related to hadith criticism done by Joseph Schact, then what is needed in this study is the literature study approach to trace the theory through the results of the analysis of various references used as reference material to find out the extent of hadith criticism made by the Orientalist who is skeptical about the authenticity of a hadith. So that in the conclusion of the hadith is not the Prophet Qaul but the results projected by the companions.